Poster Elektronik Iklan Layanan Masyarakat Bahaya Stress Pada Remaja - M. Dimas Syahputra; Heldi Heldi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Stress can be defined as a physiological and psychological response that occurs when individuals experience pressure or burdens that exceed their ability to cope. Stress in adolescents can be caused by various influencing factors such as academic demands, family problems, conflicts with peers, teenage romance and identity problems. However, teenagers still have a low understanding of the dangers of stress, in addition to the lack of optimal information through public service advertisements, especially for teenagers. The aim of the design is to build an